Preparation method and recovery method of degradable and recyclable epoxy coiled material

By reacting anhydride curing agent and epoxy resin, a degradable and recyclable epoxy coil was prepared, which solved the problem of difficult recycling of epoxy thermosetting resin industrial coils, and achieved green, efficient and value-added recycling of epoxy coils.

CN119567698APending Publication Date: 2025-03-07ZHEJIANG GANGLIU POLYMER TECH CO LTD

Patent Information

Application Number
CN202411663506.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing epoxy thermosetting resin industrial coils are difficult to achieve green and value-added recycling, resulting in waste of resources and environmental pollution.

Method used

The acid anhydride-based curing agent is used to react with the epoxy resin to produce the degradable and recoverable epoxy resin, and a degradable and recoverable epoxy coil is prepared by combining the multi-layer structure epoxy resin coating and the fiber reinforced layer.

Benefits of technology

The degradability and recovery of epoxy coils is achieved, which reduces energy consumption, reduces the use of crackers and catalysts, improves the degradation rate, and provides solutions for environmental protection and sustainable resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119567698A_ABST
    Figure CN119567698A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of functional epoxy resin industrial coiled materials, and particularly relates to a degradable and recyclable epoxy coiled material as well as a preparation method and a recycling method thereof. The invention provides an epoxy coiled material prepared by taking degradable epoxy resin as a matrix. The main components of the degradable epoxy resin comprise one or more of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether and glycerol triglycidyl ether; in addition, glutaric anhydride which helps to cure the resin and 2, 4, 6-tri (dimethylaminomethyl) phenol which helps to promote a curing reaction are compounded. According to the epoxy coiled material, degradable epoxy resin is used as an epoxy resin coating to be coated layer by layer by adopting a three-coating two-coating process method, and reinforced fibers are doped to obtain the high-strength epoxy coiled material with a multi-layer structure. The obtained epoxy coiled material is high in universality, simple in synthesis step and high in practicability and has the characteristics of being degradable and recyclable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional epoxy resin industrial coils, and in particular relates to a preparation method and a recycling method of a degradable and recyclable epoxy coil. Background Art

[0002] Since the advent of resin materials, they have been closely related to the global economy. Thermosetting epoxy resins have become increasingly important because they have superior mechanical and thermal properties than thermoplastic polymers. Epoxy membranes are emerging floor materials in the flooring industry. They are a polymer composite material prepared by a special process using a high-toughness epoxy resin matrix and a curing agent compound system as the matrix, and are toughened and reinforced by combining fibers of different materials. Because its surface layer is composed of an epoxy resin system and has high mechanical properties, epoxy membranes are highly favored in the field of building materials.

[0003] Epoxy coils are mainly composed of thermosetting polymers and high-value reinforcing materials (glass fiber, carbon fiber, polyester fiber, etc.). In actual use, epoxy coils usually need to be trimmed at their edges according to the on-site conditions, resulting in a certain amount of scraps. With the renewal of epoxy coil products and the expiration of their service life, a large number of thermosetting epoxy resin coils are about to be eliminated. Due to the lack of recyclable design, the dense cross-linked network makes it difficult for thermosetting polymers to degrade, making it difficult to recycle high-value reinforcing materials. Traditional treatment methods mainly include landfill and incineration. However, landfill methods waste resources seriously, and incineration may cause soil and water pollution. Therefore, from the perspective of environmental protection and resource utilization, it has become an urgent task to achieve green, efficient, and value-added recycling of epoxy coils. The present invention aims to solve the above problems and provide an environmentally friendly, resource-sustainable epoxy thermosetting resin industrial coil to meet future recycling and clean energy needs while minimizing environmental impact. Summary of the invention

[0004] In view of the demand for green and value-added recycling of epoxy thermosetting resin industrial coils in the prior art, the present invention provides a preparation method and recycling method of a degradable and recyclable epoxy coil. The specific technical scheme is as follows:

[0005] In a first aspect, it comprises, from bottom to top, a surface layer, a middle layer, and a bottom layer; the surface layer comprises at least one layer of epoxy resin coating; the middle layer and the bottom layer each comprise at least one fiber-reinforced layer and at least one layer of epoxy resin coating;

[0006] The epoxy resin coating comprises epoxy resin, anhydride curing agent and curing accelerator;

[0007] The epoxy resin comprises an epoxy resin matrix I and an epoxy resin matrix II, and the molar ratio between the epoxy groups in the epoxy resin matrix I and the epoxy groups in the epoxy resin matrix II is 8:1 to 1:1;

[0008] The epoxy resin matrix I is bisphenol A diglycidyl ether, and the epoxy resin matrix II is one or more of neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether and glycerol triglycidyl ether.

[0009] The acid anhydride in the acid anhydride curing agent can undergo a curing reaction with the epoxy group in the epoxy resin to generate an epoxy resin containing an ester bond, and the ester bond in the epoxy resin can undergo a dynamic chemical bond exchange reaction with the alcohol solvent, so that the high molecular weight insoluble epoxy resin is broken into a low molecular weight epoxy resin matrix soluble in the alcohol solvent, thereby realizing the recycling function. The present invention utilizes this point, uses the acid anhydride curing agent and the epoxy resin to react to obtain a degradable and recyclable epoxy resin, and uses the degradable and recyclable epoxy resin as an epoxy resin coating to prepare a degradable and recyclable epoxy coil.

[0010] On this basis, the structure of the degradable and recyclable epoxy membrane is a multi-layer structure, including a surface layer, a middle layer, and a bottom layer arranged from bottom to top. The surface layer, the middle layer, and the bottom layer are mainly obtained by coating and drying epoxy resin coatings, while reinforcing fibers are added to the middle layer and the bottom layer to improve the strength of the degradable and recyclable epoxy membrane.

[0011] Furthermore, the molar ratio between the epoxy groups in the epoxy resin matrix I and the epoxy groups in the epoxy resin matrix II is 6:1 to 1:1.

[0012] Furthermore, the molar ratio between the epoxy groups in the epoxy resin matrix I and the epoxy groups in the epoxy resin matrix II is 5:1 to 2:1.

[0013] Furthermore, the molar ratio between the epoxy groups in the epoxy resin matrix I and the epoxy groups in the epoxy resin matrix II is 4:1 to 2:1.

[0014] Furthermore, the epoxy resin also includes an epoxy resin matrix III, and the epoxy resin matrix III is bisphenol A epoxy resin and / or butyl glycidyl ether.

[0015] Furthermore, the acid anhydride curing agent is glutaric anhydride; and the molar ratio between the epoxy groups in the epoxy resin and the acid anhydride in the glutaric anhydride is 2:1 to 1:1.

[0016] Furthermore, the acid anhydride curing agent is glutaric anhydride; and the molar ratio between the epoxy groups in the epoxy resin and the anhydride in the glutaric anhydride is 1.5:1 to 1:1.

[0017] Furthermore, the acid anhydride curing agent is glutaric anhydride; and the molar ratio between the epoxy groups in the epoxy resin and the anhydride in the glutaric anhydride is 2:1 to 1.5:1.

[0018] Furthermore, the fiber reinforcement layer is glass fiber or polyester fiber.

[0019] Furthermore, the epoxy resin coating also includes one or more of color paste, additives, and fillers.

[0020] Furthermore, in parts by weight, the epoxy resin coating comprises 9 to 36 parts of epoxy resin matrix I, 6 to 20 parts of epoxy resin matrix II, 15 to 56 parts of epoxy resin matrix III, 0.5 to 2.5 parts of curing accelerator, 2 to 8 additives, 0.5 to 60 parts of filler and 0 to 10 parts of color paste; the epoxy resin matrix I is bisphenol A diglycidyl ether, the epoxy resin matrix II is one of neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether and glycerol triglycidyl ether, the epoxy resin matrix III is bisphenol A type epoxy resin and butyl glycidyl ether, the curing accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, the color paste is RAL7035, the additive is polydimethylsiloxane, bentonite or kaolin, and the filler is nano powder, talc or gas silica.

[0021] Furthermore, in parts by weight, the epoxy resin coating includes 28 to 34 parts of bisphenol A diglycidyl ether, 14 to 20 parts of neopentyl glycol diglycidyl ether, 28 to 32 parts of bisphenol A epoxy resin, 11 to 13 parts of butyl glycidyl ether, 6 to 7 parts of additives, 1.5 to 2.5 parts of curing accelerators and 0.5 to 1 part of filler.

[0022] Furthermore, in parts by weight, the epoxy resin coating comprises 16 to 19 parts of bisphenol A diglycidyl ether, 12 to 13 parts of neopentyl glycol diglycidyl ether, 19 to 21 parts of bisphenol A epoxy resin, 7 to 8 parts of butyl glycidyl ether, 2 to 3 parts of additives, 32 to 35 parts of fillers, 1 to 1.6 parts of curing accelerators and 7 to 8 parts of color pastes.

[0023] Furthermore, in parts by weight, the epoxy resin coating comprises 9 to 13 parts of bisphenol A diglycidyl ether, 8 to 9 parts of neopentyl glycol diglycidyl ether, 13 to 15 parts of bisphenol A epoxy resin, 4 to 6 parts of butyl glycidyl ether, 3 to 4 parts of additives, 50 to 55 parts of fillers, 0.7 to 1 part of curing accelerator and 3 to 4 parts of color paste.

[0024] In a second aspect, the present invention provides a method for preparing a biodegradable and recyclable epoxy coil, comprising the following steps:

[0025] S1. Epoxy resin coating is thermally cured to form a surface layer;

[0026] The surface layers of S2 and S1 are coated with epoxy resin coating, and a fiber reinforcement layer is superimposed, and a middle layer is formed on the surface layer after heat curing;

[0027] Epoxy resin coating is applied on the middle layer of S3 and S2, and a fiber reinforcement layer is superimposed. After heat curing, a bottom layer is formed on the middle layer to obtain a degradable and recyclable epoxy coil.

[0028] The present invention uses thermosetting degradable and recyclable epoxy resin as epoxy resin coating to prepare degradable and recyclable epoxy coil; wherein the epoxy resin coating can be added with color paste, filler and fiber to compound and improve the required performance of the corresponding epoxy coil layer, and the color paste can be selected and formulated according to different needs to prepare degradable and recyclable epoxy coils of different colors, so as to diversify the aesthetics of the product. In terms of technology, a three-coating and two-layering process is adopted to prepare a degradable and recyclable epoxy coil with excellent mechanical properties.

[0029] Further, the epoxy resin coating in S1 includes, by weight, 28 to 34 parts of bisphenol A diglycidyl ether, 14 to 20 parts of neopentyl glycol diglycidyl ether, 28 to 32 parts of bisphenol A epoxy resin, 11 to 13 parts of butyl glycidyl ether, 6 to 7 parts of auxiliary agent, 1.5 to 2.5 parts of curing accelerator and 0.5 to 1 part of filler;

[0030] In parts by weight, the epoxy resin coating in S2 includes 16 to 19 parts of bisphenol A diglycidyl ether, 12 to 13 parts of neopentyl glycol diglycidyl ether, 19 to 21 parts of bisphenol A epoxy resin, 7 to 8 parts of butyl glycidyl ether, 2 to 3 parts of additives, 32 to 35 parts of fillers, 1 to 1.6 parts of curing accelerators and 7 to 8 parts of color pastes;

[0031] In parts by weight, the epoxy resin coating in S3 includes 9 to 13 parts of bisphenol A diglycidyl ether, 8 to 9 parts of neopentyl glycol diglycidyl ether, 13 to 15 parts of bisphenol A epoxy resin, 4 to 6 parts of butyl glycidyl ether, 3 to 4 parts of additives, 50 to 55 parts of fillers, 0.7 to 1 parts of curing accelerators and 3 to 4 parts of color pastes.

[0032] Furthermore, in parts by weight, the epoxy resin coatings in S1, S2 and S3 include 28 to 34 parts of bisphenol A diglycidyl ether, 14 to 20 parts of neopentyl glycol diglycidyl ether, 28 to 32 parts of bisphenol A epoxy resin, 11 to 13 parts of butyl glycidyl ether, 6 to 7 parts of additives, 1.5 to 2.5 parts of curing accelerators and 0.5 to 1 part of filler.

[0033] Furthermore, in parts by weight, the epoxy resin coatings in S1, S2 and S3 include 16 to 19 parts of bisphenol A diglycidyl ether, 12 to 13 parts of neopentyl glycol diglycidyl ether, 19 to 21 parts of bisphenol A epoxy resin, 7 to 8 parts of butyl glycidyl ether, 2 to 3 parts of additives, 32 to 35 parts of fillers, 1 to 1.6 parts of curing accelerators and 7 to 8 parts of color pastes.

[0034] Furthermore, in parts by weight, the epoxy resin coatings in S1, S2 and S3 include 9 to 13 parts of bisphenol A diglycidyl ether, 8 to 9 parts of neopentyl glycol diglycidyl ether, 13 to 15 parts of bisphenol A epoxy resin, 4 to 6 parts of butyl glycidyl ether, 3 to 4 parts of additives, 50 to 55 parts of fillers, 0.7 to 1 parts of curing accelerators and 3 to 4 parts of color pastes.

[0035] Further, the epoxy resin coating in S1 includes, by weight, 28 to 34 parts of bisphenol A diglycidyl ether, 14 to 20 parts of neopentyl glycol diglycidyl ether, 28 to 32 parts of bisphenol A epoxy resin, 11 to 13 parts of butyl glycidyl ether, 6 to 7 parts of auxiliary agent, 1.5 to 2.5 parts of curing accelerator and 0.5 to 1 part of filler;

[0036] In parts by weight, the epoxy resin coatings in S2 and S3 include 16 to 19 parts of bisphenol A diglycidyl ether, 12 to 13 parts of neopentyl glycol diglycidyl ether, 19 to 21 parts of bisphenol A epoxy resin, 7 to 8 parts of butyl glycidyl ether, 2 to 3 parts of additives, 32 to 35 parts of fillers, 1 to 1.6 parts of curing accelerators and 7 to 8 parts of color pastes.

[0037] Furthermore, the time of thermal curing in S1, S2 and S3 is 30 to 50 minutes, and the temperature of thermal curing is 85 to 115°C.

[0038] In a third aspect, the present invention provides a method for recycling a degradable and recyclable epoxy coil, comprising the following steps: mixing the degradable and recyclable epoxy coil with an alcohol solvent in a mass volume ratio of 1 g: (4-5) mL, heating the mixture at 120-160° C. for 1-8.5 h to obtain a degradation liquid, further distilling the degradation liquid at 200-220° C. for 5-6 h, and removing ethylene glycol to obtain an epoxy resin dopant that can be used to prepare the degradable and recyclable epoxy coil.

[0039] Furthermore, the degradation liquid includes oligomers obtained by degradation reaction of organic raw materials for preparing degradable and recyclable epoxy coils, and inorganic raw materials for preparing degradable and recyclable epoxy coils; the organic raw materials include various kinds of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether, glycerol triglycidyl ether, bisphenol A type epoxy resin, butyl glycidyl ether, and 2,4,6-tris(dimethylaminomethyl)phenol; the inorganic raw materials include various kinds of fillers, glass fibers, and polyester fibers.

[0040] The recycling method provided by the present invention is based on the degradability and recyclability of the epoxy resin coating itself, so that almost all raw materials used to synthesize the epoxy resin coating can be recycled, including but not limited to the raw materials listed above.

[0041] Furthermore, the alcohol solvent is ethylene glycol and / or propylene glycol.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The present invention provides a method for preparing a degradable epoxy resin with strong universality, simple synthesis steps and high practicality, wherein the acid anhydride in the acid anhydride curing agent and the epoxy group in the epoxy resin matrix can undergo a curing reaction to generate an epoxy resin coating containing an ester bond, and the obtained degradable and recyclable epoxy coil has the effect of being degradable and recyclable while ensuring the normal functions of the epoxy coil;

[0044] (2) The bisphenol A diglycidyl ether, acid, ester, alcohol, 2,4,6-tris(dimethylaminomethyl)phenol, filler, glass fiber, polyester fiber and other epoxy oligomers produced during the degradation process of the recyclable epoxy resin provided by the present invention can be recycled after simple separation and purification, and can be used as a new epoxy resin-based material to prepare a new degradable and recyclable epoxy coil;

[0045] (3) Compared with the existing recovery methods that require high temperature (300°C) and the addition of strong acid, catalyst and other complex recovery processes, the recovery method provided by the present invention significantly reduces energy consumption and reduces the use of cracking agents and catalysts, while increasing the degradation rate and reducing the difficulty of reuse. Through this method, the present invention realizes green, efficient and value-added recovery of epoxy thermosetting resins and their composite materials, providing a feasible solution for environmental protection and sustainable utilization of resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 is a diagram of the degradation process of the degradable epoxy resin in Example 2;

[0047] Figure 2 This is a diagram of the regeneration process of the degradable epoxy resin in Example 2;

[0048] Figure 3 This is a diagram of the degradation process of the dual-fiber degradable epoxy coil in Example 2. DETAILED DESCRIPTION

[0049] The present invention will be further described below in conjunction with specific embodiments. The following are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto.

[0050] The sources of the materials involved in the following examples are as follows:

[0051] Among them, bisphenol A diglycidyl ether, Nan Ya NPSN901×75, and butyl glycidyl ether were all purchased from Wanqing Chemical Technology Co., Ltd.; glutaric anhydride was purchased from Guangdong Jinshengji Chemical Co., Ltd.; ZM additive (polydimethylsiloxane), ZZ additive (bentonite), ZD additive (kaolin), neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether, propylene glycol triglycidyl ether, benzyl glycidyl ether, diglycidyl ether and 2,4,6-tris(dimethylaminomethyl)phenol were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; nanopowder, talc powder, and gas silica were all purchased from Shanggao County Huagui Mining Co., Ltd.; RAL7035 light gray slurry was purchased from Suzhou Aolaixin Building Materials Co., Ltd.

[0052] [Example]

[0053] Example 1 Preparation of double-fiber biodegradable and recyclable epoxy coil

[0054] (1) Preparing the surface layer of epoxy coiled material: prepare the epoxy resin, auxiliary agent and filler required for the surface layer according to the ratio shown in Table 1, mix them evenly with a disperser, and then add glutaric anhydride and 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) and mix them evenly to prepare epoxy resin coating A. Among them, the molar ratio between the epoxy groups in epoxy resin matrix I and the epoxy groups in epoxy resin matrix II is 2:1; the molar ratio between the epoxy groups in the epoxy resin (epoxy resin matrix I, epoxy resin matrix II and epoxy resin matrix III) and the anhydride in glutaric anhydride is 1.5:1; the amount of DMP-30 is 2.2wt% of the total mass of the epoxy resin. Set the coating thickness on the coating machine to (0.35mm±0.05mm), evenly coat the epoxy resin coating A on the film with the release agent, and heat and cure it in a constant temperature drying oven at 100°C for 30 minutes to obtain the surface layer of the epoxy coiled material.

[0055] (2) Preparation of the middle layer of epoxy coiled material: the epoxy resin, auxiliary agent, filler and color paste required for the middle layer are prepared according to the proportion shown in Table 2, mixed evenly by a disperser, and then glutaric anhydride and DMP-30 are added and mixed evenly to prepare epoxy resin coating B. Among them, the molar ratio between the epoxy group in the epoxy resin matrix I and the epoxy group in the epoxy resin matrix II is 2:1; the molar ratio between the epoxy resin (epoxy resin matrix I, epoxy resin matrix II and epoxy resin matrix III) and the anhydride in glutaric anhydride is 1.5:1; the amount of DMP-30 is 2.2wt% of the total mass of the epoxy resin. The coating machine is set to a thickness of (0.6mm±0.05mm), and the epoxy resin coating B is evenly applied to the cured surface layer by the coating machine, and then the glass fiber is attached to the epoxy resin coating B, and the bubbles are naturally exhausted, and the coating is heated and cured in a constant temperature drying oven at 100°C for 30 minutes to obtain a semi-finished epoxy coiled material.

[0056] (3) Preparation of epoxy coil base layer: epoxy resin, additives, fillers and color paste required for the base layer were prepared in the proportions shown in Table 3, mixed evenly with a disperser, and then glutaric anhydride and DMP-30 were added and mixed evenly to obtain epoxy resin coating C. Among them, the molar ratio between the epoxy groups in epoxy resin matrix I and the epoxy groups in epoxy resin matrix II was 2:1; the molar ratio between the epoxy resin (epoxy resin matrix I, epoxy resin matrix II and epoxy resin matrix III) and the anhydride in glutaric anhydride was 1.5:1, and the amount of DMP-30 was 2.2wt% of the total mass of the epoxy resin. The coating thickness is set to (1.20 mm ± 0.05 mm) on the coating machine, and the epoxy resin coating C is evenly applied to the glass fiber layer of the semi-finished epoxy coil by the coating machine. The polyester fiber is then attached to the epoxy resin coating C, and the bubbles are naturally exhausted. The coating is heated and cured in a constant temperature drying oven at 100° C. for 30 minutes to obtain a double-fiber biodegradable and recyclable epoxy coil.

[0057] The raw material formula of each layer is as follows:

[0058] Table 1 Formula ratio of epoxy resin coating part A

[0059]

[0060] Table 2 Formula ratio of epoxy resin coating part B

[0061]

[0062]

[0063] Table 3 Formula ratio of epoxy resin coating part C

[0064]

[0065] Example 2

[0066] (1) Weigh 60 g of the double-fiber biodegradable and recyclable epoxy coil obtained in Example 1, put it into 250 mL of ethylene glycol solution, and completely degrade it at 160° C. for 30 min. Then, the temperature is raised to 200° C. and distilled at 200° C. for 5 h to completely volatilize the ethylene glycol solution therein, thereby obtaining an epoxy resin degradation liquid without ethylene glycol, which is recorded as ERSO.

[0067] (2) Bisphenol A diglycidyl ether and ERSO were mixed in different proportions to obtain a new resin system (wherein the amount of ERSO added was 10 to 30 wt% of the new resin system), glutaric anhydride was used as a curing agent (wherein the molar ratio of the epoxy group in the new resin system to the anhydride in glutaric anhydride was 1.5:1), and after the above substances were mixed evenly, DMP-30 was added (the amount of DMP-30 added was 2.2 wt% of the total mass of the new resin system) to prepare regenerated degradable epoxy resins using epoxy resin degradation liquid as raw material, which were recorded as RER-10 wt%, RER-20 wt% and RER-30 wt%, respectively.

[0068] Example 3

[0069] (1) Preparing the surface layer of epoxy coiled material: prepare the epoxy resin, auxiliary agent and filler required for the surface layer according to the ratio shown in Table 1, mix them evenly with a disperser, and then add glutaric anhydride and 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) and mix them evenly to prepare epoxy resin coating A. Among them, the molar ratio between the epoxy groups in epoxy resin matrix I and the epoxy groups in epoxy resin matrix II is 2:1; the molar ratio between the epoxy groups in the epoxy resin (epoxy resin matrix I, epoxy resin matrix II and epoxy resin matrix III) and the anhydride in glutaric anhydride is 1.5:1; the amount of DMP-30 is 2.2wt% of the total mass of the epoxy resin. Set the coating thickness on the coating machine to (0.35mm±0.05mm), evenly coat the epoxy resin coating A on the film with the release agent, and heat and cure it in a constant temperature drying oven at 100°C for 30 minutes to obtain the surface layer of the epoxy coiled material.

[0070] (2) Prepare the middle layer of the epoxy coil, set the thickness on the coating machine to (0.6 mm ± 0.05 mm), and use the coating machine to evenly apply the epoxy resin coating A prepared in (1) on the cured surface layer, then attach the glass fiber to the epoxy resin coating A, naturally exhaust the bubbles, heat and cure in a constant temperature drying oven at 100° C. for 30 minutes to obtain a semi-finished epoxy coil.

[0071] (3) Prepare the epoxy coil base layer, set the thickness on the coating machine to (1.20 mm ± 0.05 mm), and use the coating machine to evenly apply the epoxy resin coating A prepared in (1) on the glass fiber layer of the semi-finished epoxy coil. Then, attach the polyester fiber to the epoxy resin coating A, naturally exhaust the bubbles, and heat and cure it in a constant temperature drying oven at 100° C. for 30 minutes to obtain a double-fiber biodegradable and recyclable epoxy coil.

[0072] Table 1 Formula ratio of epoxy resin coating part A

[0073]

[0074] Example 4

[0075] (1) Preparation of the surface layer of epoxy coil: The epoxy resin, auxiliary agent and filler required for the surface layer are prepared in the proportions shown in Table 2, mixed evenly with a disperser, and then glutaric anhydride and 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) are added and mixed evenly to prepare epoxy resin coating A1. Among them, the molar ratio between the epoxy groups in the epoxy resin matrix I and the epoxy groups in the epoxy resin matrix II is 2:1; the molar ratio between the epoxy groups in the epoxy resin (epoxy resin matrix I and epoxy resin matrix II) and the anhydride in glutaric anhydride is 1.5:1; and the amount of DMP-30 is 2.2wt% of the total mass of the epoxy resin. The coating thickness is set to (0.35mm±0.05mm) on the coating machine, and the epoxy resin coating A1 is evenly coated on the film with the release agent, and heated and cured in a constant temperature drying oven at 100°C for 30 minutes to obtain the surface layer of the epoxy coil.

[0076] (2) Preparation of the middle layer of epoxy coiled material: prepare the epoxy resin, auxiliary agent and filler required for the middle layer according to the proportion shown in Table 3, mix them evenly with a disperser, and then add glutaric anhydride and DMP-30 to mix evenly to prepare epoxy resin coating B1. Among them, the molar ratio between the epoxy groups in the epoxy resin matrix I and the epoxy groups in the epoxy resin matrix II is 2:1; the molar ratio between the epoxy resin (epoxy resin matrix I and epoxy resin matrix II) and the anhydride in glutaric anhydride is 1.5:1; the amount of DMP-30 is 2.2wt% of the total mass of the epoxy resin. The coating machine is set to a thickness of (0.6mm±0.05mm), and the epoxy resin coating B1 is evenly applied to the cured surface layer with the coating machine, and then the glass fiber is attached to the epoxy resin coating B1, and the bubbles are naturally exhausted, and the coating is heated and cured in a constant temperature drying oven at 100°C for 30 minutes to obtain a semi-finished epoxy coiled material.

[0077] (3) Prepare the epoxy coil base layer, set the thickness on the coating machine to (1.20 mm ± 0.05 mm), and use the coating machine to evenly apply the epoxy resin coating B1 prepared in (2) on the glass fiber layer of the semi-finished epoxy coil. Then, attach the polyester fiber to the epoxy resin coating B1, naturally exhaust the bubbles, and heat and cure it in a constant temperature drying oven at 100° C. for 30 minutes to obtain a double-fiber biodegradable and recyclable epoxy coil.

[0078] Table 2 Partial formula ratio of epoxy resin coating A1

[0079]

[0080] Table 3 Partial formula ratio of epoxy resin coating B1

[0081]

[0082] Example 5

[0083] (1) Preparing the surface layer of epoxy coil, the epoxy resin required for the surface layer is prepared according to the molar ratio of epoxy groups in bisphenol A diglycidyl ether and epoxy groups in neopentyl glycol diglycidyl ether being 2:1, mixed evenly with a disperser, and then glutaric anhydride and 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) are added and mixed evenly to prepare epoxy resin coating A2. Among them, the molar ratio of epoxy groups in epoxy resin (bisphenol A diglycidyl ether and neopentyl glycol diglycidyl ether) and anhydride in glutaric anhydride is 1.5:1; the amount of DMP-30 is 2.2wt% of the total mass of epoxy resin. The coating thickness is set to (0.35mm±0.05mm) on the coating machine, and the epoxy resin coating A2 is evenly coated on the film with the release agent, and heated and cured in a constant temperature drying oven at 100°C for 30 minutes to obtain the surface layer of the epoxy coil.

[0084] (2) Prepare the middle layer of the epoxy coil, set the thickness on the coating machine to (0.6 mm ± 0.05 mm), and use the coating machine to evenly apply the epoxy resin coating A2 prepared in (1) on the cured surface layer, then attach the glass fiber to the epoxy resin coating A2, naturally exhaust the bubbles, heat and cure in a constant temperature drying oven at 100° C. for 30 minutes to obtain a semi-finished epoxy coil.

[0085] (3) Prepare the epoxy coil base, set the thickness on the coating machine to (1.20 mm ± 0.05 mm), and use the coating machine to evenly apply the epoxy resin coating A2 prepared in (1) on the glass fiber layer of the semi-finished epoxy coil. Then, attach the polyester fiber to the epoxy resin coating A2, naturally exhaust the bubbles, and heat and cure it in a constant temperature drying oven at 100° C. for 30 minutes to obtain a double-fiber biodegradable and recyclable epoxy coil, denoted as DE.2:1 :GA 1.5:1 .

[0086] Example 6

[0087] This embodiment is basically the same as Embodiment 5, except that neopentyl glycol diglycidyl ether is replaced by pentaerythritol tetraglycidyl ether / trimethylolpropane triglycidyl ether / propylene triglycidyl ether, and other conditions remain unchanged, thereby obtaining a plurality of double-fiber biodegradable and recyclable epoxy coils.

[0088] Example 7

[0089] This example is basically the same as Example 5, wherein the molar ratios of the epoxy groups in bisphenol A diglycidyl ether and the epoxy groups in neopentyl glycol diglycidyl ether are 8:1, 5:1, 3:1, 2.5:1 and 4:3, and the other conditions remain unchanged, and a plurality of double-fiber biodegradable and recyclable epoxy coils (respectively referred to as samples DE 8:1 ,DE 5:1 ,DE 3:1 ,DE 2.5:1 and DE 4:3 ).

[0090] Example 8

[0091] This example is basically the same as Example 5, wherein the molar ratios of the epoxy group in the epoxy resin (bisphenol A diglycidyl ether and neopentyl glycol diglycidyl ether) and the anhydride in the glutaric anhydride are 2:1 and 1:1, respectively, and the other conditions remain unchanged, and a plurality of double-fiber biodegradable and recyclable epoxy coils (respectively referred to as samples GA and GA) are obtained. 2:1 and GA 1:1 ).

[0092] Comparative Example 1

[0093] (1) Preparing the surface layer of the epoxy coil: bisphenol A diglycidyl ether, glutaric anhydride and 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) were uniformly mixed to obtain epoxy resin coating A3. The molar ratio of the epoxy group in bisphenol A diglycidyl ether to the anhydride in glutaric anhydride was 1.5:1; the amount of DMP-30 was 2.2wt% of the mass of bisphenol A diglycidyl ether. The coating thickness was set to (0.35mm±0.05mm) on the coating machine, and the epoxy resin coating A3 was uniformly coated on the film with the release agent, and heated and cured in a constant temperature drying oven at 100°C for 30 minutes to obtain the surface layer of the epoxy coil.

[0094] (2) Prepare the middle layer of the epoxy coil, set the thickness on the coating machine to (0.6 mm ± 0.05 mm), and use the coating machine to evenly apply the epoxy resin coating A3 prepared in (1) on the cured surface layer, then attach the glass fiber to the epoxy resin coating A3, naturally exhaust the bubbles, heat and cure in a constant temperature drying oven at 100° C. for 30 minutes to obtain a semi-finished epoxy coil.

[0095] (3) Prepare the epoxy coil base layer, set the thickness on the coating machine to (1.20 mm ± 0.05 mm), and use the coating machine to evenly apply the epoxy resin coating A3 prepared in (1) on the glass fiber layer of the semi-finished epoxy coil. Then, attach the polyester fiber to the epoxy resin coating A3, naturally exhaust the bubbles, and heat and cure it in a constant temperature drying oven at 100° C. for 30 minutes to obtain a double-fiber biodegradable and recyclable epoxy coil.

[0096] Comparative Example 2

[0097] This comparative example is basically the same as Example 5, except that neopentyl glycol diglycidyl ether is replaced by benzyl glycidyl ether or diglycidyl ether), and other conditions remain unchanged to obtain a double-fiber biodegradable and recyclable epoxy coil.

[0098] Comparative Example 3

[0099] This comparative example is basically the same as Example 5, wherein the molar ratios of the epoxy groups in bisphenol A diglycidyl ether and the epoxy groups in neopentyl glycol diglycidyl ether are 1:2 and 9:1, and the other conditions remain unchanged to obtain a plurality of double-fiber biodegradable and recyclable epoxy coils (respectively referred to as samples DE 1:2 and DE 9:1 ).

[0100] Comparative Example 4

[0101] This comparative example is basically the same as Example 5, except that the molar ratios of the epoxy group in the epoxy resin (bisphenol A diglycidyl ether and neopentyl glycol diglycidyl ether) and the anhydride in the glutaric anhydride are 1:2 and 3:1, and the other conditions remain unchanged to obtain a plurality of double-fiber biodegradable and recyclable epoxy coils (respectively referred to as samples GA and GA). 1:2 and GA 3:1 ).

[0102]

Performance test

[0103] The indicator detection methods in this section are as follows:

[0104] The pencil hardness of the samples was tested according to the test standard “GB-T 6739-2022 Paints and varnishes - Determination of film hardness by pencil method”. The instrument used was an automatic pencil hardness tester (ST-5608, Xiamen, China).

[0105] The Shore D hardness of the sample was tested according to the standard "GB T 2411-2008 Plastics and hard rubber - Determination of indentation hardness using a hardness tester".

[0106] The bending property of the samples was tested according to the standard GB / T 11982.1-2015 Polyvinyl chloride roll flooring Part 1: Non-homogeneous polyvinyl chloride roll flooring, and the instrument used was a bending tester (QTY-32, Shanghai, China).

[0107] 1. Degradation and recycling performance

[0108] The RER-10wt%, RER-20wt% and RER-30wt% obtained in Example 2 were tested for pencil hardness and Shore hardness. The results are shown in Table 4.

[0109] Table 4 Hardness test of three kinds of regenerated biodegradable epoxy resins

[0110]

[0111] From the results in Table 4, it can be seen that when the addition amount of ERSO is 10-30wt%, the pencil hardness of the corresponding regenerated biodegradable epoxy resin can reach H; and when the addition amount of ERSO is 20wt%, the Shore hardness reaches the maximum, which is 80.2.

[0112] 2. Effect of epoxy resin matrix on the performance of biodegradable epoxy membrane

[0113] ①The role of epoxy resin matrix III

[0114] The double-fiber biodegradable and recyclable epoxy coils obtained in Example 1, Example 3, Example 4, Example 5, and Comparative Example 1 were tested for pencil hardness, Shore hardness, and toughness. The results are shown in Table 5.

[0115] Table 5 Performance comparison of different biodegradable epoxy membranes

[0116]

[0117]

[0118] The pencil hardness of the coils of three different structures in Example 1, Example 3 and Example 4 are 2H, H and 2H respectively, and the Shore hardness is 80, 68 and 76 respectively; it shows that as the amount of filler added increases, the hardness performance of the coil is improved, but the curling performance can be around a 40mm circular axis 180° without cracks.

[0119] By comparing the performance of the coils prepared in Example 3 and Example 5, the pencil hardness is H, the Shore hardness is 68 and 67 respectively, and the curling performance can be around a 40mm circular axis 180° without cracks, indicating that the epoxy resin matrix III and a trace amount of filler have little effect on the hardness and curling performance of the coil.

[0120] By comparing the performance of the coil prepared in Example 5 and Comparative Example 1, the pencil hardness is H and 2H respectively, and the Shore hardness is 67 and 83 respectively. However, the curling performance of Comparative Example 1 is poor and easy to break. This formula does not meet the basic properties of the coil, indicating that the addition of epoxy resin II can greatly improve the curling degree of the coil.

[0121] ②Selection of epoxy resin matrix II type

[0122] The double-fiber biodegradable and recyclable epoxy coils obtained in Example 5, Example 6, and Comparative Example 2 were tested for pencil hardness, Shore hardness, and toughness. The results are shown in Table 6.

[0123] Table 6 Performance comparison of different biodegradable epoxy membranes

[0124]

[0125] Neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether and glycerol triglycidyl ether can all be used as the source of epoxy resin matrix II, and the prepared epoxy coil exhibits high hardness and high bending degree. When other glycerol ethers are selected, the bending degree of the environmental coil cannot be guaranteed, so the selection of epoxy resin matrix II is not arbitrary.

[0126] ③ The molar ratio between the epoxy groups in epoxy resin matrix I and the epoxy groups in epoxy resin matrix II

[0127] The double-fiber biodegradable and recyclable epoxy coils obtained in Example 5, Example 7 and Comparative Example 3 were tested for pencil hardness, Shore hardness and toughness. The results are shown in Table 7.

[0128] Table 7 Performance comparison of different biodegradable epoxy membranes

[0129]

[0130] By comparing Example 5 and Example 7, it is found that as the amount of epoxy resin II added gradually increases, the hardness of the coil tends to gradually decrease, but its curling degree remains excellent, and when the ratio of epoxy resin I to epoxy resin II is greater than 8:1, cracks will gradually begin to appear in the coil. Among them, when the ratio of epoxy resin I to epoxy resin II is 2:1, its comprehensive performance is most suitable for making coils.

[0131] ④ The molar ratio of epoxy groups in epoxy resin to anhydride in glutaric anhydride

[0132] The double-fiber biodegradable and recyclable epoxy coils obtained in Example 5, Example 8, and Comparative Example 4 were tested for pencil hardness, Shore hardness, and toughness. The results are shown in Table 8.

[0133] Table 8 Performance comparison of different biodegradable epoxy membranes

[0134]

[0135]

[0136] From the comparison of the coil performance of Example 5 and Example 8, it can be seen that the hardness performance of the coil is increased by the addition ratio of glutaric anhydride to DE 2:1 :GA 1.5:1 When the ratio of epoxy resin to glutaric anhydride is greater than 3:1 or less than 1:2, the Shore hardness of the coil is lower than the instrument measurement value and has no practical significance.

Claims

1. A biodegradable and recyclable epoxy coil, characterized in that: It includes a surface layer, a middle layer and a bottom layer from bottom to top; the surface layer includes at least one layer of epoxy resin coating; the middle layer and the bottom layer each include at least one fiber reinforcement layer and at least one layer of epoxy resin coating; The epoxy resin coating comprises epoxy resin, anhydride curing agent and curing accelerator; The epoxy resin comprises an epoxy resin matrix I and an epoxy resin matrix II, and the molar ratio between the epoxy groups in the epoxy resin matrix I and the epoxy groups in the epoxy resin matrix II is 8:1 to 1:1; The epoxy resin matrix I is bisphenol A diglycidyl ether, and the epoxy resin matrix II is one or more of neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether and glycerol triglycidyl ether.

2. The biodegradable and recyclable epoxy coil according to claim 1, characterized in that: The epoxy resin further comprises an epoxy resin matrix III, and the epoxy resin matrix III is bisphenol A type epoxy resin and / or butyl glycidyl ether.

3. The degradable and recyclable epoxy coil according to claim 1 or 2, characterized in that: The acid anhydride curing agent is glutaric anhydride, and the molar ratio between the epoxy groups in the epoxy resin and the acid anhydride in the glutaric anhydride is 2:1 to 1:

1.

4. The biodegradable and recyclable epoxy coil according to claim 2, characterized in that: The epoxy resin coating further comprises one or more of color paste, additives and fillers.

5. The biodegradable and recyclable epoxy coil according to claim 4, characterized in that: The epoxy resin coating comprises, by weight, 9 to 36 parts of epoxy resin matrix I, 6 to 20 parts of epoxy resin matrix II, 15 to 56 parts of epoxy resin matrix III, 0.5 to 2.5 parts of curing accelerator, 2 to 8 parts of auxiliary agents, 0.5 to 60 parts of filler and 0 to 10 parts of color paste; the epoxy resin matrix I is bisphenol A diglycidyl ether, the epoxy resin matrix II is one of neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether and glycerol triglycidyl ether, the epoxy resin matrix III is bisphenol A type epoxy resin and butyl glycidyl ether, the curing accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, the color paste is RAL7035, the auxiliary agent is polydimethylsiloxane, bentonite or kaolin, and the filler is nano powder, talc or gas silica.

6. The biodegradable and recyclable epoxy coil according to claim 1, characterized in that: The fiber reinforcement layer is glass fiber or polyester fiber.

7. A method for preparing a biodegradable and recyclable epoxy coil according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Epoxy resin coating is thermally cured to form a surface layer; The surface layers of S2 and S1 are coated with epoxy resin coating, and a fiber reinforcement layer is superimposed, and a middle layer is formed on the surface layer after heat curing; Epoxy resin coating is applied on the middle layer of S3 and S2, and a fiber reinforcement layer is superimposed. After heat curing, a bottom layer is formed on the middle layer to obtain a degradable and recyclable epoxy coil.

8. The preparation method according to claim 7, characterized in that: The time of thermal curing in S1, S2 and S3 is 30 to 50 minutes, and the temperature of thermal curing is 85 to 115°C.

9. A method for recycling a biodegradable and recyclable epoxy coil according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing a degradable and recyclable epoxy coil with an alcohol solvent in a mass volume ratio of 1 g: (4-5) mL, heating the mixture at 120-160° C. for 1-8.5 h to obtain a degradation liquid; continuously distilling the degradation liquid at 200-220° C. for 5-6 h, and removing ethylene glycol to obtain an epoxy resin doping material that can be used to prepare the degradable and recyclable epoxy coil.

10. The recycling method according to claim 9, characterized in that: The degradation liquid includes oligomers obtained by degradation reaction of organic raw materials for preparing degradable and recyclable epoxy coils, and inorganic raw materials for preparing degradable and recyclable epoxy coils; the organic raw materials include multiple types of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether, glycerol triglycidyl ether, bisphenol A type epoxy resin, butyl glycidyl ether, and 2,4,6-tris(dimethylaminomethyl)phenol; the inorganic raw materials include multiple types of fillers, glass fibers, and polyester fibers.

Citation Information

Patent Citations

  • Epoxy resin composition and fiber-reinforced composite material

    CN104080856A

  • Epoxy resin composition, cured product, fiber-reinforced composite material, prepreg, and tow prepreg

    CN113874441A

  • Resin composition, cured resin product, and fiber-reinforced resin

    CN116457388A

  • Preparation method and application of recyclable epoxy resin composite material cured by glutaric anhydride

    CN118834373A

  • Hydrophobic anti-corrosion industrial coiled material floor

    CN220686601U

Cited By

  • Scratch self-repairing type epoxy coiled material as well as preparation method and repairing method thereof

    CN121471658A